Subband Adaptive Equalisation For Wireless Communications - Ng, Yin Hoe (2007)
Motivated by the notable success of subband decomposition techniques for adaptive filtering applications, we propose a novel, robust subband adaptive chip equalising (SAGE) receiver as an effective solution for performance enhancement over time-dispersive direct-sequence ultra wideband (DS-UWB) and DS-CDMA downlinks. Since the proposed receiver works at the chip level instead of symbol level, it can also be applied to systems that deploy long scrambling codes.